PARTICIPATION OF NON-PARTY STAKEHOLDERS IN THE IMPLEMENTATION OF PARIS AGREEMENT TOWARDS COP26 - Kimp Yustisiana Dewinta Hermawan (Padjadjaran Journal of International Law, 2021)
This article deals with the participation of Non-party Stakeholders (NPS) in implementing the Paris Agreement. Paris Agreement is an agreement within the United Nations Framework Convention on Climate Change (UNFCCC) signed in 2016. The 26th Conference of the Parties (COP26) has been delayed due to pandemics and will be conducted in November 2022 in Glasgow. However, the member states have not showcased any progress in its implementation. The method of this research is normative-analytical. Despite the roles of NPS are enhanced compared to its arrangement in Kyoto Protocol, the target of the Paris Agreement is not on track where there are member states who have not submitted their updated Nationally Determined Contribution (NDC). Hence, the upcoming COP26 is expected to result progressive advancement of member states towards the implementation of Paris Agreement. The enhancement of Non-Party Stakeholders’ participation is deemed as a crucial factor in achieving the Paris Agreement’s goals. In this article, I argue that even if the agreement does not directly bind NPS, the participation of NPS can be realized and enhanced to advance the achievement of Paris Agreement’s goals, especially towards COP26 through national legislations of the member states that obliged NPS to cooperate and participate actively. Thus, the principle of cooperation is also applicable towards NPS.